Youth at risk: a prevention resource for counselors, teachers and parents - Capuzzi, Dave (American Counseling Association, 2008)
Defining youth at risk / Douglas R. Gross and David Capuzzi -- Prevention : an overview / David Capuzzi and Douglas R. Gross -- Resiliency : individual, family, school and community perspectives / Rolla E. Lewis -- The impact of dysfunctional family dynamics on children and adolescents / Cass Dykeman -- "Who cares what I think" : problems of low self-esteem / Sandra S. Meggert -- Preventing and treating mood disorders in children and adolescents / Benedict T. McWhirter and Karrie P. Walters -- Stress and trauma : coping in today's society / Jane E. Rheineck and Russell D. Miars -- "I'll cry tomorrow" : diverse youth and the scars that don't show / Laura R. Simpson and Jeannie Falkner -- The secret and all-consuming obsessions : eating disorders / Kimberly Wright and Elva E. Blanks -- "I don't want to live" : the adolescent at risk for suicidal behavior / David Capuzzi and Douglas R. Gross -- A future in jeopardy : sexuality issues in adolescence / Melinda Haley and Jason Vasquez -- "I am somebody" : gang membership / Lisa Langfuss Aasheim and Sonya C. Burnham -- Counseling queer youth : preventing another Matthew Shepard and Gwen Araujo story / Fernando J. Gutierrez -- Death in the classroom : violence in schools / Abbe Finn -- "I can't live without it" : adolescent substance abuse / Camea J. Gagliardi-Blea... [et al.] -- Nowhere to turn : the young face of homelessness / Melissa A. Stormont and Rebecca B. McCathren -- "This isn't the place for me" : school dropout / Lea R. Flowers and Mary A. Hermann